2015
DOI: 10.1021/acscatal.5b01835
|View full text |Cite
|
Sign up to set email alerts
|

Significant Contribution of Intrinsic Carbon Defects to Oxygen Reduction Activity

Abstract: While the carbon-based metal-free electrocatalysts for oxygen reduction reaction (ORR) have experienced great progress in recent years, the fundamental issue on the origin of ORR activity is yet far from being clarified. To date, the ORR activities of these electrocatalysts are usually attributed to different dopants, while the contribution of intrinsic carbon defects has been little touched. Herein, we report the high ORR activity of the defective carbon nanocages, which is better than that of the B-doped car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
417
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(436 citation statements)
references
References 41 publications
9
417
1
9
Order By: Relevance
“…Such relatively high desulfurization activity could be attributed to the high stability of the defect decorated with oxygenated functional groups on the OGFs-16 catalyst which are generated at a relatively high treatment temperature, i.e., 250 • C. Similar results have also been reported by the HNO 3 treated carbon nanotubes (CNTs) which is expected to bear the same active center [16]. Jiang et al [50] have reported that pure carbon nanocages, which possess abundant holes, edges, and positive topological disclinations display a relatively good oxygen reductive performance which is even better than those reported for undoped CNTs. In the present work, the control of the macroscopic shape of the OGFs catalyst represents also a net advantage as the catalyst shape can be modified in a large range depending to the downstream applications.…”
Section: Ogfs As Metal-free Catalyst For Selective Oxidation Of H 2 Smentioning
confidence: 59%
“…Such relatively high desulfurization activity could be attributed to the high stability of the defect decorated with oxygenated functional groups on the OGFs-16 catalyst which are generated at a relatively high treatment temperature, i.e., 250 • C. Similar results have also been reported by the HNO 3 treated carbon nanotubes (CNTs) which is expected to bear the same active center [16]. Jiang et al [50] have reported that pure carbon nanocages, which possess abundant holes, edges, and positive topological disclinations display a relatively good oxygen reductive performance which is even better than those reported for undoped CNTs. In the present work, the control of the macroscopic shape of the OGFs catalyst represents also a net advantage as the catalyst shape can be modified in a large range depending to the downstream applications.…”
Section: Ogfs As Metal-free Catalyst For Selective Oxidation Of H 2 Smentioning
confidence: 59%
“…2b) [120] with DFT calculations indicating that pentagon and zigzag edge defects were responsible for the observed high ORR activity for the defective carbon nanocages (Fig. 2c) [120]. Recently, defective graphene (DG) materials have also been prepared from N-doped precursors using a facile nitrogen removal procedure (Fig.…”
Section: Defect-induced Charge Transfermentioning
confidence: 92%
“…Well-defined pore distributions and defects can affect the catalytic activity of carbon-based catalysts [111,112,[119][120][121][122]. In 2015, Jin et al reported a new class of ORR catalysts based on graphene quantum dots supported by graphene nanoribbons with ORR performances comparable to or even better than that of Pt/C electrodes [119].…”
Section: Defect-induced Charge Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…2b exhibits that the hole size was nearly 20 nm. These holes would expose more extra active edge sites for ORR and bring better performance [34,35]. The surface area from the BET experiments also proved that, after the acid washing, the surface area of MPSA-Co-900-Acid (124 m 2 g −1 ) was a little higher than that of MPSA-Co-900 (102 m 2 g −1 ), which would bring more active sites.…”
Section: Resultsmentioning
confidence: 88%